Murabahah and Entrepreneurial Factors Driving MSME Growth in Sidoarjo: Murabahah dan Faktor Kewirausahaan yang Mendorong Pertumbuhan UMKM di Sidoarjo - Susetyo, Qotrunnada Aisyah Mega; Rahmawati , Imelda Dian (Indonesian Journal of Innovation Studies, 2025)
General background: Micro, Small, and Medium Enterprises (MSMEs) are vital drivers of Indonesia’s economic resilience, particularly in sustaining employment and regional income distribution. Specific background: Despite their contribution, many MSMEs in Sidoarjo struggle to grow due to limited access to capital, weak entrepreneurial characteristics, and inadequate marketing strategies. Knowledge gap: Previous studies rarely integrated Islamic financing instruments, entrepreneurial behavior, and marketing strategies in one comprehensive model to explain MSME growth. Aims: This study aims to examine how Murabahah contracts, entrepreneurial characteristics, business capital, and marketing strategies contribute to MSME development in Sidoarjo Regency. Results: Using multiple linear regression with 62 food and beverage MSME respondents, all four variables showed a significant positive relationship with MSME growth. Novelty: The integration of Murabahah financing within a holistic model of MSME development demonstrates how Islamic economic values strengthen business sustainability. Implications: The findings emphasize the importance of syariah-based financial accessibility, improved entrepreneurial competence, and adaptive marketing strategies to enhance local economic empowerment. Highlights: Murabahah financing fosters sustainable MSME growth. Entrepreneurial character strongly supports competitiveness. Marketing innovation enhances regional economic resilience. Keywords: Murabahah, Entrepreneurial Characteristics, Business Capital, Marketing Strategy, MSME Development